Redescription of Crossvallia Unienwillia: the only Paleocene Antarctic Penguin - Jadwiszczak, Piotr; Acosta Hospitaleche, Carolina Ileana Alicia; Reguero, Marcelo Alfredo (Ameghiniana)
Redescribed and reinterpreted here is a partial skeleton of the oldest Antarctic penguin, Crossvallia unienwillia from the late Paleocene of Marambio (Seymour) Island. A thorough morphological analysis of limb bones (humerus, femur and tibiotarsus) allowed us to report both an amended reconstruction of type specimens and a revised taxonomic diagnosis of this large-sized early penguin. Moreover, an additional skeletal element, a single thoracic vertebra, is described for the first time. C. unienwillia is characterized by a mixture of features typical of both geologically older and younger penguins, supplemented by characters that are obviously unique. The above-mentioned findings shed new light on the very beginning of penguin evolution. REDESCRIPCIÓN DE CROSSVALLIA UNIENWILLIA: LA ÚNICA ESPECIE ANTÁRTICA DE PINGÜINO PALEOCENO. Se redescribe e interpreta el esqueleto parcial de Crossvallia unienwillia, el pingüino antártico más antiguo, del Paleoceno superior de la Isla Marambio (Seymour). Un minucioso análisis morfológico de los elementos apendiculares (húmero, fémur y tibiotarso) permitió enmendar la reconstrucción del holotipo y revisar la diagnosis de esta especie primitiva de gran talla. Además, un elemento adicional del esqueleto, una vértebra torácica, es descripta por primera vez. C. unienwillia se caracteriza por una combinación de caracteres típicos de pingüinos más primitivos y más modernos, sumado a sus atributos particulares. Estos hallazgos permiten contar con nueva evidencia acerca de la evolución temprana de los pingüinos. Fil: Jadwiszczak, Piotr. Uniwersytet w Białymstoku; Polonia Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Reguero, Marcelo Alfredo. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de ...